2021
DOI: 10.1002/2050-7038.13083
|View full text |Cite
|
Sign up to set email alerts
|

State‐observer based IDD controller for concurrent frequency‐voltage control of a hybrid power system with electric vehicle uncertainties

Abstract: Summary The present paper proposes a novel state‐observer (SO) based integral‐double‐derivative controller for simultaneous frequency‐voltage control operation of a hybrid power system. The hybrid system consists of solar‐thermal, conventional‐thermal, diesel‐plant, and modern day electric vehicle (EV), establishing a concurrent system frequency, voltage, and the corresponding tie‐line power control. In order to exhibit realistic approach, the hybrid system is provided with appropriate system non‐linearities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…The importance of EVs in enhancing the system stability of a HPS is presented by the authors of References 10 and 22. To examine the influence of EVs on the stability of the established HPS, EVs in area‐1 are detached.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of EVs in enhancing the system stability of a HPS is presented by the authors of References 10 and 22. To examine the influence of EVs on the stability of the established HPS, EVs in area‐1 are detached.…”
Section: Resultsmentioning
confidence: 99%
“…[4][5][6][7][8]10,12,15,16,[19][20][21] However, due to rising complexity, conventional controllers don not achieve desired responses. In this regard, advanced control approaches 22,[28][29][30][31][32][33] are used by authors to overcome the limitations in conventional control strategy. In Reference 28, the authors have proposed a sliding-mode based controlling strategy for frequency control of HPS.…”
Section: Related Literature and Gapsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, EVs are proving to be good option in reducing carbon emissions 46 . The widespread use of EVs opens up the possibility of grid frequency control and reduce the conventional generation units power output 47,48 . However, very few research articles are reported on system dynamics control of EV incorporated deregulated power system.…”
Section: Introductionmentioning
confidence: 99%
“…Renewable based LFC of a hybrid power system and electric cars are outlined in References 33 and 34. The impacts of electric vehicles on system load demand for a multiarea hybrid power system were illustrated by the authors in Reference 35. However, the impact of EV on LFC‐AVR coupled operation requires more investigation.…”
Section: Introductionmentioning
confidence: 99%